Bending properties of 3D printed coconut wood-PLA composite. Issue 5 (January 2020) - Kesavarma, S; Kong, C K; Samykano, M; Kadirgama, K; Pandey, A K
Abstract: Fused Deposition Modelling (FDM) is an additive manufacturing technology that has been utilized in developing numerous components from various material for various application. However, in particular, the properties of PLA embedded with coconut wood are still limited. Coconut wood is well known for its environmentally friendly, biodegradable materials, thermal resistance and corrosion resistance. Therefore, the purpose of this research is to investigate the properties of Coconut wood-PLA at different infill percentage (25%, 50%, 75%) and infill pattern (Rectilinear, honeycomb, grid, concentric and octagram spiral) by using FDM technique. The infill percentage refers to the amount of material in percentage used to print corresponding infill patterns. The specimen is printed according to ASTM D790. After that, the bending test been carried out to investigate the mechanical properties. Two mechanical properties were analyzed which are flexural strength and flexural modulus. After the experiment, the results obtained are then further analyzed by using response surface methodology to determine which parameter gives significant effect to mechanical properties. Mathematical models of the mechanical properties were also introduced using response surface methodology which can be used to predict desired mechanical properties with varying infill percentage and infill pattern. The results show that concentric infill pattern and 75% infill percentage achieved maximum properties in bending testing. The optimum parameters combination is concentric infill pattern with 75% infill percentage. Its optimum mechanical property is 22.666MPa for flexural strength and 0.4823GPa for flexural modulus.